Assessing GNSS integrity augmentation techniques in UAV sense-and-avoid architectures - Sabatini, Roberto; Moore, Terry; Hill, Chris (2015)
The integration of Global Navigation Satellite System (GNSS) integrity augmentation functionalities in Unmanned Aerial Vehicles (UAV) Sense-and-Avoid (SAA) architectures has the potential to provide an integrity-augmented SAA solutiThe integration of Global Navigation Satellite System (GNSS) integrity augmentation functionalities in Unmanned Aerial Vehicles (UAV) Sense-and-Avoid (SAA) architectures has the potential to provide an integrity-augmented SAA solution suitable for cooperative and non-cooperative scenarios. In this paper, we evaluate the opportunities offered by this integration, proposing a novel approach that maximizes the synergies between Avionics Based Integrity Augmentation (ABIA) and UAV cooperative/non-cooperative SAA architectures. In the proposed architecture, the risk of collision is evaluated by setting a threshold on the Probability Density Function (PDF) of a Near Mid-Air Collision (NMAC) event over the separation area in both cooperative and non-cooperative cases. When the specified thresholds are exceeded, an avoidance manoeuvre is performed by implementing a heading-based Differential Geometry (DG) or Pseudospectral (PS) optimization to generate a set of optimal trajectory solutions free of near mid-air conflicts. The selection of DG or PS is based on the time available to perform the avoidance maneuver as dictated by the relative dynamics of the host and intruder platforms. The trajectory is optimized by implementing a cost function with minimum time constraints and fuel penalty criteria weighted as a function of separation distance. The optimised avoidance trajectory also considers the constraints imposed by the ABIA in terms of UAV platform dynamics and GNSS constellation satellite elevation angles and thus prevents degradation or loss of navigation data during Track, Decide and Avoid (TDA) processes of a SAA loop. Therefore, real-time trajectory corrections are performed to re-establish the Required Navigation Performance (RNP) when actual GNSS accuracy degradations and/or data losses take place. The performance of this Integrity- Augmented SAA (IAS) architecture was evaluated by simulation case studies involving cooperative and non-cooperative scenarios. The selected host platform was the AEROSONDE UAV and the simulation cases were performed in a representative crosssection of the UAV operational flight envelope. Simulation results demonstrate that the proposed IAS architecture is capable of performing high-integrity conflict detection and resolution when GNSS is considered as the primary source of navigation data.